Effects of cylindrical and conical heights on pressure and velocity fields in cyclones - Demir, Selami; Karadeniz, Aykut; Aksel, Murat (Elsevier Science Bv, Po Box 211, 1000 AE Amsterdam, Netherlands, 2016)
Nine modifications of Stairmand high-efficiency type cyclone with various cylindrical and conical heights were used to investigate their effects on pressure drop and flow field within cyclones. An experimental setup was built and experiments were conducted on various cyclone geometries at inlet velocities ranging from 10 to 185 m/s. The body heights ranged from D to 2D (D being the diameter of the cyclone body), while the conical heights were between 2D and 3D. The experimental results were used to calibrate CFD (Computational Fluid Dynamics) model. Experimental results showed that the pressure drop ranged from 191 to 235 Pa and 690 to 920 Pa at the lowest and highest inlet velocities, respectively, and that pressure drop is a function of both cylindrical and conical heights with reduced pressure drops as cylindrical and/or conical heights increase. Maps showing the change in pressure drop with respect to cylindrical and conical heights were prepared and interpreted to determine optimum ratio of conical-to-cylindrical height for reduced pressure drop. Optimum ratio was found experimentally as between 1.67 and 2.5. CFD results agreed well with the experimental data and the results helped gain insights into complicated phenomena taking place in cyclones. CFD results showed that increased axial velocities at the lip of vortex finder distrub radial velocity profiles and that tangential velocities in the stabilized vortex can be as high 1.4 times the mean inlet velocity. Both findings indicate that collection efficiency of the cyclone may be influenced by the height of the cyclone. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Cyclones; Cylindrical/Conical height; CFD; Pressure fields; Velocity fields; Artificial Neural-Networks; Genetic Algorithms; Cfd Simulation; Gas Cyclones; Flow-Field; Optimization; Performance; Separators; Geometry; Drop